الإحتراق النفسي لدى المحامي الجزائري - قعيرة,وردة; بحري,صابر (University of Eloued جامعة الوادي, 2025)
هدفت الدراسة إلى التعرف على الإحتراق النفسي لدى المحامي الجزائري وفق بعض المتغيرات من خلال التعرف على أثر متغير الجنس، الخبرة المهنية، الحالة الإجتماعية، السن على مستوى الإحتراق النفسي، ولتحقيق أهداف الدراسة تم إستخدام المنهج الوصفي لمناسبته طبيعة وموضوع الدراسة، وقد تم إستخدام مقياس ماسلاس للإحتراق النفسي كأداة لجميع البيانات والمعلومات في الدراسة، وتكونت عينة الدراسة من 148 محام، وبعد توزيع أداة الدراسة وتجميعها تم إستخدام المعالجات الإحصائية(المتوسط الحسابي، الإنحراف المعياري، إختبار T)، ولقد أظهرت النتائج المتوصل إليها أن هناك فروق ذات دلالة إحصائية في الإحتراق النفسي لدى المحامي تعز لمتغير الجنس، في حين تم التوصل أنه لا توجد فروق ذات دلالة إحصائية في الإحتراق النفسي لكل من الحالة الإجتماعية، الخبرة المهنية، السن. Abstract: The study aimed to identify psychological burnout among Algerian lawyers according to some variables by identifying the effect of the variables of gender, professional experience, marital status, and age on the level of psychological burnout. To achieve the objectives of the study, the descriptive approach was used to suit the nature and topic of the study, and the Maslas scale was used. For psychological burnout as a tool for all data and information in the study, the study sample consisted of 148 lawyers, and after distributing and assembling the study tool, statistical treatments were used (arithmetic mean, standard deviation, T-test), and the results obtained showed that there are statistically significant differences in psychological burnout. In Lawyer Taiz, the gender variable was determined, while it was found that there were no statistically significant differences in psychological burnout for marital status, professional experience, and age
Keywords: Psychological Burnout; stress and agitation; lack of a sense of accomplishment; الإحتراق النفسي; الإجهاد الإنفعالي; نقص الشعور بالإنجاز